INNOVATION COMMUNICATION IN BUILDING A SUSTAINABLE BAMBOO CRAFT INDUSTRY TO FULFILL ASEAN PRIORITIES ECONOMIC DELIVERABLES: A CASE STUDY OF STUDIO DAPUR - Ovaldo, Rafellino; Novianty, Siti Juhriah; Witono, Andika (JURNAL SIGNAL, 2024)
To communicate innovation is one of the main drivers of growth in the bamboo industry to be sustainable. Implementing innovative ideas into practice is a challenge, as every party such as production, designer and even stakeholders should have the same objectives for achieving the goals. Innovation communication is important to break the old paradigm and face new challenges, misunderstanding has to be reduced, in order for new products to be created. Moreover, it is one of the major catalysts behind new ideas and concepts taking root within an organization. Studio Dapur, a social enterprise, is working with the best bamboo artists to create a sustainable, mutual, and inclusive bamboo craft sector. This also supports Indonesia as the Chair of ASEAN 2023 where Indonesia wants to bring ASEAN into an area that has an important role for regional countries and the world, especially as a centre of economic growth, the engine of peace, and regional prosperity. To make this happen, three pillars of Priorities Economic  Deliverables have been developed. As a result, effective innovation communication plays a crucial role in breaking old paradigms, overcoming challenges, and fostering the creation of new bamboo products. By embracing innovative ideas and involving multiple stakeholders, Studio Dapur sets an example for the industry and contributes to the economic growth, peace, and regional prosperity envisioned by ASEAN.